Interrelationships Between Psychosocial, Motivational, and Psychological Processes for Effective Learning: A Structural Equation Modeling Study - Phan, Huy P.; Ngu, Bing H. (Frontiers in Psychology, 2021)
We tested a theoretical-conceptual model that introduced our recently developed psychological concept, termed as psychological processes, which is defined as “a person’s continuing frame of mind to focus on disposition towards strong resolute, structured thoughts and organization, and aspiration to strive for educational success”. This proposition is innovative as it considers the notion that a person’s mindset is malleable and, importantly, subjects to social experiences derived from a situated social context. Moreover, from our definition, we contend that psychological processes, as a distinct construct, is ‘latent’, or underlying, with three comparable psychological attributes: personal resolve, effective functioning, and personal striving. Our conceptualization, acknowledging the importance of social contexts and individualized experience and personal belief, proposed that perceived social experiences (i.e., positive versus negative), as a source of information, would shape a student’s psychological processes, his/her state of motivation, and engagement in different types of adaptive outcomes. Moreover, from our point of view, psychological processes would act as a predictor as well as a potential mediator of motivation and engagement in different types of adaptive outcomes. In a similar vein, from the positive effect of psychological processes, motivation could act as a predictor as well as a mediator of adaptive outcomes. Structural equation modeling, from Taiwanese university students’ (N = 739) responses to various Likert-scale measures, showed support for our original a priori model – for example, the positive effects of perceived social experiences on psychological processes (β = .81, p < .001) motivation (β = .61, p < .001), and adaptive outcomes (β = .36, p < .01), and the positive effect of psychological processes on motivation (β = .31, p < .01). Interestingly, we also found some interesting findings with regard to the effects of measured indicators – for example, the positive effect of personal resolve, as a measured indicator, on adaptive outcomes (β = .28, p < .001), and the effect of self-efficacy, as a measured indicator, on academic liking experience, also a measured indicator (β = .12, p < .01).